Impact of Diabetic Polyneuropathy on Ventilatory Function and Respiratory Muscle Endurance - Darwish, Moshera H.; Mohamed, Sandra. A; Mostafa, Marwa; Khalifa, Heba (International Journal of Psychosocial Rehabilitation, 2020)
Diabetic polyneuropathy is one of the most common complications associated with diabetes mellitus. Respiratory neuromuscular function may be affected in diabetic polyneuropathy in type II diabetes. To determine impact of diabetic polyneuropathy on ventilatory function and respiratory muscle endurance. A cross sectional study was performed on ninety type II diabetic patients and thirty matched normal subjects from both genders. Their age ranged from 40 to 60 years. The duration of illness was at least five years. The subjects were assigned into two groups; normal subjects (control group (G1) and diabetic patients (study group (G2). The study group was subdivided into three equal subgroups; (G2a) represented diabetic patients without neuropathy; (G2b) included diabetic patients with clinically diagnosed neuropathy and (G2c) included diabetic patients with confirmed neuropathy diagnosed by nerve conduction studies (NCS). Severity of diabetic polyneuropathy was assessed and rated according to Toronto Clinical Neuropathy Scoring System (TCNS) and confirmed by NCS. Ventilatory function (forced vital capacity, forced expiratory volume in one second and forced expiratory volume in one second / forced vital capacity ratio (FEVI/FVC) and respiratory muscle strength (peak expiratory flow) and endurance (maximal voluntary ventilation) were assessed by Jaeger Vyntus IOS spirometer. revealed significant decrease in all measured variables in both (G2b) and (G2c) comparing with (G1) and (G2a) except FEVI/FVC ratio which is similar in four groups. A negative correlation was observed between the scores of TCNS and all measures of respiratory functions and between the age and MVV. Diabetic polyneuropathy in type II diabetes has a negative effect on pulmonary function.